Hydroxytyrosol Acetate Inhibits Vascular Endothelial Cell Pyroptosis via the HDAC11 Signaling Pathway in Atherosclerosis - Yao, Feng; Jin, Zhen; Lv, Xiaohan; Zheng, Zihan; Gao, Hongqian; Deng, Ying; Liu, Yizhen; Chen, Lifang; Wang, Weirong; He, Jianyu; Gu, Jianli; Lin, Rong (Frontiers in Pharmacology, 2021)
Hydroxytyrosol acetate (HT-AC), a natural polyphenolic compound in olive oil, exerts an anti-inflammatory effect in cardiovascular diseases (CVDs). Pyroptosis is a newly discovered form of programmed inflammatory cell death and is suggested to be involved in the atherosclerosis (AS) process. However, the effect of HT-AC on vascular endothelial cell pyroptosis remains unknown. Thus, we aimed to investigate the effect of HT-AC on vascular endothelial cell pyroptosis in AS and related signaling pathways. In vivo studies showed that HT-AC alleviated the formation of atherosclerotic lesions and inhibited pyroptosis in the aortic intima of ApoE-/- mice fed a high-fat diet (HFD) for 12 weeks. In vitro, we found that HT-AC treatment of human umbilical vein endothelial cells (HUVECs) alleviated tumor necrosis factor-alpha (TNF-α)-induced pyroptosis by decreasing the number of PI positive cells, decreasing the enhanced protein expressions of activated caspase‐1 and gasdermin D (GSDMD), as well as by decreasing the release of pro-inflammatory interleukin (IL)‐1β and IL‐6. Besides, HT-AC down-regulated HDAC11 expression in the aortic intima of HFD-fed ApoE-/- mice and TNF-α-stimulated HUVECs. To determine the underlying mechanism of action, molecular docking and drug affinity responsive target stability (DARTS) were utilized to identify whether HDAC11 protein is a target of HT-AC. The molecular docking result showed good compatibility between HT-AC and HDAC11. DARTS study's result showed that HDAC11 protein may be a target of HT-AC. Further study demonstrated that knockdown of HDAC11 augmented the inhibition of HT-AC on pyroptosis in TNF-α-stimulated HUVECs. These findings indicate that HT-AC might prevent vascular endothelial pyroptosis through down-regulation of HDAC11 related signaling pathway in AS.